Analisis Warehouse Management System (WMS) dari Platform Jubelio pada Gudang CV. ABC - Wijayanti, Asti Diah; Yun, Yun (Ekonomis: Journal of Economics and Business, 2025)
This study aims to evaluate the effectiveness of implementing the Warehouse Management System (WMS) from the Jubelio platform in the warehouse of CV. ABC, a Small and Medium Enterprise (SME) operating in the retail apparel sector. The research employs the Failure Mode and Effect Analysis (FMEA) approach to identify and analyze key risks affecting warehouse operational efficiency. The findings reveal that although WMS adoption has reduced manual recording errors, challenges remain, such as inventory data inaccuracies, device integration limitations, and insufficient staff training. Based on the FMEA analysis, the highest-priority risks include inventory recording errors, delays in data updates, and discrepancies between digital stock data and physical stock conditions.